2018
DOI: 10.1371/journal.pone.0207319
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of potential prognostic and predictive miRNAs of epithelial ovarian cancer

Abstract: BackgroundOvarian cancer is the leading cause of death by gynecologic cancers in the Western world. The aim of the study was to identify microRNAs (miRNAs) associated with prognosis and/or resistance to chemotherapy among patients with epithelial ovarian cancer.MethodsUsing information from the Pelvic Mass Study we identified a cohort of women with epithelial ovarian cancer. Tumor tissues were then collected and analyzed by global miRNA microarrays. MiRNA profiling was then linked to survival and time to progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…Numerous studies have shown that miRNA can be used to predict the prognosis of patients with ovarian cancer [85]. Gao et al [86] collected serum samples from 74 patients with epithelial ovarian cancer, 19 patients with borderline ovarian cancer, and 50 healthy controls, and they determined the levels of miR-200c and miR-142 by quantitative PCR.…”
Section: Prognosis Of Mirna and Ovarian Cancermentioning
confidence: 99%
“…Numerous studies have shown that miRNA can be used to predict the prognosis of patients with ovarian cancer [85]. Gao et al [86] collected serum samples from 74 patients with epithelial ovarian cancer, 19 patients with borderline ovarian cancer, and 50 healthy controls, and they determined the levels of miR-200c and miR-142 by quantitative PCR.…”
Section: Prognosis Of Mirna and Ovarian Cancermentioning
confidence: 99%
“…Many studies have been conducted to search for cancer biomarkers using mRNA from cryopreserved ovarian tissue or section staining of the tissue with antibodies [ 16 , 18 , 34 , 35 ]. Different research groups have started conducting studies to search for circulating miRNAs [ 36 , 37 ] or miRNAs in the tissue [ 20 , 38 , 39 , 40 ] as specific cancer biomarkers, but a study of miRNA expression after cryopreservation has just been recently published [ 19 ]. This study showed that upregulated miRNA–24 and downregulated expression of miRNA–193b, miRNA–320A, and steroid production could be non-invasive (expression patterns in culture media) markers for cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, currently, disparities in steroid production and altered expression of specific microRNAs (miRNAs), e.g., miRNA–193b, miRNA–320A, and miRNA–24, after cryopreservation have been associated with failure of ovarian tissue functioning and folliculogenesis [ 19 ]. MicroRNAs are a class of small non–coding RNA molecules that have been shown to be potential biomarkers for different cancers and prognostics [ 20 ] and are involved in gametogenesis, embryo development, and fertility [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have emphasized the core position of miRNAs in governing cancer development (13,14). miR-1183 was reported to be dysregulated in numerous human diseases (15)(16)(17) and Zhou et al (18) reported that miR-1183 functioned in the tumorigenesis of NSCLC. Nevertheless, the precise mechanism of miR-1183 in NScLc progression remains to be studied.…”
Section: Introductionmentioning
confidence: 99%